Evaluation of LAMP for detection and/or screening of Leptospira spp. infection among domestic animals in the Philippines - Tubalinal, Gabriel Alexis SP.; Balbin, Michelle M.; Villanueva, Marvin A.; Domingo, Clarissa Yvonne J.; Mingala, Claro N. (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: This study assessed the applicability of loop-mediated isothermal amplification (LAMP) for the detection of leptospirosis among domesticated animals and sewage rats. Specifically, it evaluated the ability of LAMP to amplify Leptospira spp. targeting the 16s rRNA gene in boiled urine samples. Materials and methods: A total of 140 samples from different domestic animals were tested for the presence of the antigen. A nested-polymerase chain reaction (nPCR) protocol was used to compare and determine the sensitivity of LAMP in detecting Leptospira spp. The LAMP was also evaluated by comparing its amplification result using agarose gel electrophoresis and color change using dye. Results: Positivity rate of Leptospira spp. antigen was 29.0% (40/140) for LAMP and 9.3% (13/140) for nPCR. Also, LAMP results for gel electrophoresis and dye color change varied in some samples that may be due to the interpretation of the result in dye color change. Conclusion: Overall, LAMP is a rapid, sensitive, and cost-effective diagnostic method compared with nPCR. Also, LAMP has a potential application as pen-side screening, surveillance, and clinical diagnostic kits of infectious diseases without requiring advance equipment and skilled personnel. http://doi.org/10.5455/javar.2018.e299